In-plane strength of unreinforced masonry piers. - Calderini, Chiara
The definition of adequate simplified models to assess the in-plane load-bearing capacity of masonry piers, in terms of both strength and displacement, plays a fundamental role in the seismic verification of masonry buildings. In this paper, a critical review of the most widespread strength criteria present in the literature and codes to interpret the failure modes of piers (rocking, crushing, bed joint sliding or diagonal cracking) are proposed. Models are usually based on an approximate evaluation of the stress state produced by the external forces in a few points/sections and on its assessment with reference to a limit strength domain. The aim of the review is to assess their reliability by discussing the hypotheses, which they are based on (assumed stress states; choice of reference points/sections on which to assess the pier strength; characteristics of the limit strength domain) and to verify the conditions for their proper use in practice, in terms of both stress fields (depending on the geometry of the pier, boundary conditions and applied loads) and types of masonry (i.e. regular brick masonry vs rubble stone masonry). In order to achieve these objectives, parametric nonlinear finite element analyses are performed and different experimental data available in the literature are analysed and compared.
Keywords: Masonry; Pier strength; In-plane behaviour; Seismic capacity; Failure mechanisms; Simplified models